Natural disaster mitigation system with an IoT based TTGO T-Call V1.3 ESP32 wireless module microcontroller / Muhammad Fareez Asyraf Istas Fahrurrazi - Fahrurrazi, Muhammad Fareez Asyraf Istas (2024)
The Natural Disaster Mitigation System project employs the TTGO T-CALL V1.3 ESP32 WIRELESS MODULE MICROCONTROLLER to develop an advanced monitoring system addressing deficiencies in Malaysia's current disaster monitoring infrastructure. Real-time environmental data is collected and transmitted to an HTTP server for analysis through the integration of sensors like accelerometers and ultrasonic devices The project utilizes the ESP32-WROVER-B microcontroller and incorporates the LAMP (Linux, Apache, MySQL, PHP) stack for comprehensive monitoring and response capabilities. The prototype system involves input and output components, including sensors, LEDs, buzzers, and an LCD display, with software specifications using Arduino IDE. The methodology entails gathering sensor data, evaluating it with a decision-making algorithm, triggering alarms, activating output devices, and transmitting data to the server via HTTP protocols. The expected outcomes include continuous monitoring, accurate anomaly detection, and timely alerts based on predefined thresholds, all facilitated by the robust data management capabilities of the LAMP